Keefektifan Implementasi Psikoterapi Islam Dalam Mengatasi Problematika Psikologis Anak Usia Remaja - Ach. Choiron; Dian Triana (FAI- Undar, 2021)
In the present we see many things in the field of work, marriage, human relations and social life. This is a stimulus and inspiration for the use of psychotherapy in the fields of psychological, social work, religion, leadership and law enforcement. The fact of pervasive emotional illness into the structure of individual character has expanded the goal of psychotherapy, neither saving nor a change of symptoms leading to damaged health patterns of human relationships. In this case the psychotherapist can be a means in the structure of structure and character change. This research is an attempt to know the application of Islamic psychotherapy how to overcome the psychological problems of adolescent children. The main questions to be answered through this research: How is the concept of Islamic psychotherapy in overcoming the psychological problems of adolescent children? How to apply Islamic psychotherapy in overcoming the psychological problems of teenage children? Is the effectiveness of Islamic psychotherapy can overcome the psychological problems of adolescents? To answer the question, this researcher uses qualitative approach with study design (research and development). The study findings suggest that parents have some therapies. In therapy one of the methods used is religious psychotherapy. Religious psychotherapy or more accurately called Islamic psychotherapy is a method of treating the disease by further raising awareness of the remembrance of Allah through the guidance of the Qur'an and As Sunnah. This is in addition to facilitate the disease can also be closer to Allah SWT. Of them complain of personal problems, while for teenagers more to the problem of character, mental, social, study and family. In general, the implementation of psychotherapy of adolescents other than through religious paths such as prayer, dhikr, tawassul, prayer, fasting, mau'idloh / advice and so on, in addition to the need for supervision and assistance specifically to let the process more quickly, such as such as the search for skills and other activities, can also be helped by psychiatrists, kiyai or others who can provide healing solutions.